Evaluation of taVNS for extreme environments: an exploration study of health benefits and stress operationality - Le Roy, Barbara; Martin-Krumm, Charles; Gille, Adèle; Jacob, Sandrine; Vigier, Cécile; Laborde, Sylvain; Claverie, Damien; Besnard, Stéphane; Trousselard, Marion (Frontiers in Neurology, 2023)
Introduction Long-duration space missions will be a real challenge for maintaining astronauts' adaptability. Research on transcutaneous vagus nerve stimulation (taVNS) is expanding rapidly, and its modalities constitute a major research challenge. A growing number of reviews stress the need to validate biomarkers for monitoring effects to enhance our understanding of the processes by which taVNS acts. Heart rate variability (HRV) appears to be a relevant candidate that informs on the autonomic nervous system (ANS). This is a promising technique to minimize the pathogenic effects of such large-scale missions and thus might be a relevant countermeasure. This study aimed to investigate the impact of taVNS on cognitive, psychological, and physiological functioning, including ANS functioning, and the benefits of increasing the number of taVNS sessions. Method A total of 44 healthy participants were randomly assigned to one of the two cross-over protocols: a single session protocol (one taVNS and one sham simulation) or a repeated session protocol (three taVNS and three sham simulations). Cognitive, psychological, and physiological measures were performed before (pre) and after (post) each intervention. Sleep monitoring was only recorded before the first and after the last intervention in each protocol. For the repeated session protocol only, participants were allocated to two groups according to their parasympathetic activation gain during the three interventions: high parasympathetic delta (HPd) and low parasympathetic delta (LPd). Results Participants in the repeated session protocol increased their HRV, cognitive performance, and sleep efficiency. In particular, taVNS induced higher parasympathetic activation and cardiac flexibility compared to the sham simulation in the repeated session protocol. Nevertheless, the perception of stress may indicate a nocebo effect of the repeated session. The HPd profile had higher interoceptive awareness, HRV highlighted by non-linear measures, and cognitive performance, but presented a decrease in some indicators of sleep efficiency compared to the LPd profile. Conclusion taVNS seems to induce positive health outcomes, especially when the stimulation is repeated three times per week. Our findings highlight the benefits of parasympathetic activation during taVNS on psychophysiological and cognitive functioning. Further research is needed to validate these results on a large sample, using longitudinal measures over several months. This intervention appears promising as a countermeasure to extreme missions and occupations.